Atribut Minuman Teh Kemasan Siap Minum yang Memengaruhi Persepsi Konsumen di Kabupaten Tegal - Dias Indrasti; Fina Siliyya (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2022)
Ready-to-drink packaged tea drinks have various attributes affecting consumer perception. This study aims to identify the attributes of ready-to-drink packaged tea drinks that became the main concern, considered important, and affecting purchasing decisions by consumers in Tegal Regency. The method used was a purposive sampling survey. Data were analyzed by chi-square tests. The survey involved 150 respondents, which majority was woman (60.00%), aged 15-24 year (68.67%), had diploma/bachelor degree (54.67%), worked as student (50.67%), and earned less than Rp1,000,000 (62.67%) per month. As many as 93.34% respondent bought packaged tea drinks at minimarkets and grocery stalls for themselves (45.33%) and family (50.00%). Purchase made with a frequency of 1-2 times a week (35.33%) to once a month (40.66%). The attributes of packaged tea drinks were taste and aroma (38.67%), halal (29.33%), and expiration date (13.33%). The attributes of packaged tea drinks considered as very important were halal (92.67%), expiration date (82.00%), and taste and aroma (61.33%). Attributes of packaged tea drinks affecting purchasing decisions were taste and aroma (98.67%), expiration date (98.00%), and halal (96.67%). Taste and aroma was the main attributes that influence the perception of respondents in Tegal Regency in buying packaged tea beverage products.